스텝을 활용한 인지-운동프로그램이 경도인지장애 노인의 인지기능, 보행, 우울에 미치는 효과 - 주은솔; 방요순; 오은주; Ju, Eunsol; Bang, Yosoon; Oh, Eunju (Journal of the Korean Society of Integrative Medicine, 2020)
Purpose : The purpose of this study was to determine the effects of a cognitive-exercise program using step on the cognitive function, gait, and depression of elderly with mild cognitive impairment. Methods : The subjects comprised 30 elderly people with mild cognitive impairment who used elderly welfare centers in the provinces A, B, and C between March 21 and June 7, 2019. They were divided into an experimental group (n=15) and a control group (n=15) before undergoing an experiment based on a pretest-posttest control group design. The lowenstein occupational therapy cognitive assessment-geriatric population was used to assess the subjects' cognitive function, while the 4-stage balance test, 30-second chair-stand test, timed up & go test, and functional reach test were employed to evaluate their gait. In addition, the beck depression inventory was used to measure their levels of depression. Results : The cognitive-exercise program using step enhanced the subjects' cognitive function and gait and reduced their levels of depression. Furthermore, statistically significant differences were found between the experimental group and the control group. Conclusion : The cognitive-exercise program using step promoted the process of sensorimotor and cognition through the learning process of various steps taking left and right steps and cognitive activities. It improves gait by activating the coordination of the musculoskeletal and nervous systems of the body and positively affecting posture control, balance, flexibility, and lower extremity muscles. It also relieved depression by performing successful step learning and cognitive activities with forward-looking (doing) that leads to pleasure and achievement. The present study confirmed the value of a cognitive-exercise program using step to treat multiple domains of functional decline in elderly patients with mild cognitive impairment. This is therefore proposed as an intervention program for this patient group.